Novel drug delivering conduit for peripheral nerve regeneration. (13th November 2017) - Labroo, Pratima; Shea, Jill; Edwards, Kyle; Ho, Scott; Davis, Brett; Sant, Himanshu; Goodwin, Isak; Gale, Bruce; Agarwal, Jay
Abstract: Objective . This paper describes the design of a novel drug delivery apparatus integrated with a poly lactic-co-glycolic acid (PLGA) based nerve guide conduit for controlled local delivery of nerve growth factor (NGF) and application in peripheral nerve gap injury. Approach . An NGF dosage curve was acquired to determine the minimum in vitro concentration for optimal neurite outgrowth of dorsal root ganglion (DRG) cells; PLGA based drug delivery devices were then designed and tested in vitro and in vivo across 15 mm rat sciatic nerve gap injury model. Main results . The drug delivery nerve guide was able to release NGF for 28 d at concentrations (0.1–10 ng ml −1 ) that were shown to enhance DRG neurite growth. Furthermore, the released NGF was bioactive and able to enhance DRG neurite growth. Following these tests, optimized NGF-releasing nerve conduits were implanted across 15 mm sciatic nerve gaps in a rat model, where they demonstrated significant myelination and muscle innervation in vivo as compared to empty nerve conduits ( p < 0.05). This drug delivery nerve guide can release NGF for extended periods of time and enhance axon growth in vitro and in vivo and has the potential to improve nerve regeneration following a peripheral nerve injury. Significance . This integrated drug delivering nerve guide simplifies the design process and provides increased versatility for releasing a variety of different growth factors. This innovative device has the potential for broad applicability and allows for easier customization to change the type of drugs and dosage of individual drugs without devising a completely new biomaterial–drug conjugate each time.